The Practical Aspects and Relevance of the Texts of ‘Patterns for College Writing’ in Nepalese Context - Gartaula, Sudeep (KMC Research Journal, 2021)
‘Patterns for College Writing’ (Twelfth Edition) is a prescribed textbook under Tribhuvan University compulsory English for four years program of B.A./B.A.S.W. and B.B.S. level first year students. The textbook is also studied by millions of students at colleges and universities across the United States. The problem is that being composed by US writers, published by US publications and written in the US context, many Nepali students are thinking this book is irrelevant and impractical to Nepalese society. A question can be raised why this book is prescribed for Nepali students. This paper aims to address these problems and satisfy the students by discovering the practical aspects of the texts included in the textbook. Therefore, this brief academic study analyzes how the textbook ‘Patterns for College Writing’ can address various issues of Nepali public lives, which are: a) Socio-cultural issue b) Historical issue c) Health related issue d) Gender and racial issue. This paper aims to highlight the fact that the contents of this textbook, which are mostly written in American context and contain various essays on American issues, are relevant and useful in Nepalese context as well.